FAKTOR FISIK KIMIA LINGKUNGAN PENDUKUNG KEANEKARAGAMAN DAN KEMERATAAN HOLOTHUROIDEA PADA ZONA INTERTIDAL DESA HILA KECAMATAN KEPULAUAN ROMANG KABUPATEN MALUKU BARAT DAYA - Sriyanti I. A. Salmanu (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: The sea is an ecosystem that has high biodiversity. Hila Village is one area that has a large enough waters located in the western part of Romang island, District of Romang Islands, Southwest Maluku District. Intertidal Zone Hila Village has different types of substrate, both muddy, sandy, sandy, dreamy, rocky, rocky, sandy, rocky, and rocky rocked. The existence of the types of sea cucumbers (Holothuroidea) in the coastal waters of Hila village quite a lot, physical chemical environmental factors in the coastal waters of Hila Village support the life of the sea cucumber. Method: This research is descriptive research that reveal information about environmental characteristic (temperature, pH, salinity, and dissolved oxygen), diversity and evenness of sea cucumber in intertidal zone of Hila Village. Results: The results of the research on the intertidal zone of Hila Village, Pulau Romang Subdistrict, Southwest Maluku District, were found 7 genus and 8 spesies. The types of Holothuroidea found in the study sites are Bohadschia argus, Holothuria atra, Holothuria edulis, Bohadschia marmorata, Holothuria scraba, Chiridota violaceae, Holothuria fuscopunctata, and Opheodesoma spectabili. The Holothuroidea diversity index in the Intertidal Zone of Hila Village is 1.56, categorized by medium diversity, for evenly distributed evenness because the fairness index is 1.05. Conclusion: The index of the Holothuroidea diversity in the Intertidal Zone of Hila Village is 1.56, categorized by medium diversity, for evenly distributed evenness because the fairness index is 1.05. Chemical Physical Factors The envelope found was the average temperature of 28.270C, the average pH 6.373, and the average salinity of 4.94%, indicating that the Holothuroidea was able to adapt and live in the intertidal zone of Hila Village.